Implementation of Differentiated Instruction in Increasing Student Participation with Different Learning Styles - Nur Patria Pujitama Sari; Reviandari Widyatiningtyas; Nuzul Tenriana (PT. Anagata Sembagi Education, 2025)
This study aims to describe the implementation of Differentiated Instruction (DI) by teachers at SMP Negeri 1 Kongbeng and its impact on the participation of students with different learning styles. Departing from the challenge of learning style diversity that is often overlooked in conventional teaching approaches, this study emphasizes the importance of adaptive and responsive strategies to students' individual needs. Using a descriptive qualitative approach, data were collected through in-depth interviews, classroom observations, and documentation studies of teaching materials. The results showed that teachers began to implement differentiation in content, processes, and learning products, but the implementation was still varied and limited. Inhibiting factors included limited training, administrative burden, and lack of structural support and policies that supported DI. However, several local innovations such as learning stations began to show positive impacts on student engagement. These findings underline that the success of DI depends not only on the method, but also on the teacher's pedagogical competence and systemic support. Therefore, the implementation of DI requires synergy between increasing teacher capacity, reforming education policies, and providing adequate resources in order to realize equitable, participatory, and transformative learning, especially in the context of non-urban schools such as SMP Negeri 1 Kongbeng.